Two Distinct Domains within CIITA Mediate Self-Association: Involvement of the GTP-Binding and Leucine-Rich Repeat Domains - Linhoff, Michael W. (American Society for Microbiology, 2001)
CIITA is the master regulator of class II major histocompatibility complex gene expression. We present evidence that CIITA can self-associate via two domains: the C terminus (amino acids 700 to 1130) and the GTP-binding domain (amino acids 336 to 702). Heterotypic and homotypic interactions are observed between these two regions. Deletions within the GTP-binding domain that reduce GTP-binding and transactivation function also reduce self-association. In addition, two leucine residues in the C-terminal leucine-rich repeat region are critical for self-association as well as function. This study reveals for the first time a complex pattern of CIITA self-association. These interactions are discussed with regard to the apoptosis signaling proteins, Apaf-1 and Nod1, which share domain arrangements similar to those of CIITA.